1995
DOI: 10.1002/aja.1002020208
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic potential of the avian somite

Abstract: We have studied the angiogenic potential of the unsegmented paraxial mesoderm and epithelial somites of the trunk with homotopical grafts between quail and chick embryos. Quail endothelial cells of the grafts were stained with the QH-1 antibody after 1-6 days of reincubation. The unsegmented paraxial mesoderm and all parts of the epithelial somite were found to contain angioblasts which develop into QH-1 positive endothelial cells. These cells are incorporated into the lining of the host's blood vessels such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
111
0
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(123 citation statements)
references
References 42 publications
8
111
0
4
Order By: Relevance
“…Quail-chick chimeras were analyzed using QH1 to identify vessels deriving from grafts, and the source of endothelial cells contributing to the PNVP and vessels invading the neural tube was shown to be primarily lateral plate mesoderm, with contributions from somitic angioblasts. [7][8][9] We extended these studies by analyzing mouse-quail chimeras that had orthotopic grafts of mouse somitic mesoderm in quail hosts. 10 These studies showed that mouse angioblasts could also migrate and contribute to the PNVP in the avian embryo, indicating that the neural-derived patterning cues crossed species.…”
Section: Neurovascular Development Moves Forwardmentioning
confidence: 99%
“…Quail-chick chimeras were analyzed using QH1 to identify vessels deriving from grafts, and the source of endothelial cells contributing to the PNVP and vessels invading the neural tube was shown to be primarily lateral plate mesoderm, with contributions from somitic angioblasts. [7][8][9] We extended these studies by analyzing mouse-quail chimeras that had orthotopic grafts of mouse somitic mesoderm in quail hosts. 10 These studies showed that mouse angioblasts could also migrate and contribute to the PNVP in the avian embryo, indicating that the neural-derived patterning cues crossed species.…”
Section: Neurovascular Development Moves Forwardmentioning
confidence: 99%
“…Expression in the dorsal neural tube, IM, and LPM remains the same throughout development. Numerous angioblasts are reported to be present in the lateral part of the somite, participating in the formation of the blood and lymphatic vessel in the limb and ventro-lateral body wall (Lance-Jones, 1988;Noden, 1989;Wilting et al, 1995). Thus, expression of Vasohibin in lateral plate and limb mesoderm might reflect a possible role in the regulation of angioblast migration from the somite.…”
Section: During Chick Embryogenesismentioning
confidence: 99%
“…In all regions, EC are exclusively derived from mesoderm, be it segmented (trunk) 14 or unsegmented (head). 15 Of note, the dorsal aortas arise as paired structures from confluent blood islands and subsequently fuse into a single aorta along the a-p axis.…”
Section: Cellular and Regional Diversity Of Mesenchyme Around Cnsmentioning
confidence: 99%
“…The latter will give rise to striated muscles and dermis, whereas the former will give rise to the vertebral column. In addition to these fates, cells of all somite compartments 14,19,20 (and not blood islands), will give rise to EC in the body wall and extremities-and in the NT. In addition, PC and vSMC can also be derived from somite cells.…”
Section: Cellular and Regional Diversity Of Mesenchyme Around Cnsmentioning
confidence: 99%
See 1 more Smart Citation